2020
DOI: 10.33019/agrosainstek.v4i1.109
|View full text |Cite
|
Sign up to set email alerts
|

Analisis komparatif kandungan metabolit pada daun mutan tanaman Torbangun (Plectranthus amboinicus (Lour.) Spreng.)

Abstract: Torbangun (Plectranthus amboinicus) merupakan tanaman obat dari keluarga Lamiaceae. Pada masyarakat Batak, daun torbangun digunakan untuk meningkatkan produksi air susu. Keragaman kandungan fitokimia dapat ditingkatkan salah satunya dengan teknik iradiasi sinar gamma untuk program pemuliaan tanaman. Pada penelitian ini, metode metabolomik yang tidak tertarget digunakan untuk mengevaluasi profil senyawa pada bagian daun tanaman mutan dari iradiasi sinar gamma dan kontrol. Kandungan senyawa planlet mutan dan kon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Based on morphological changes, one putative mutant for P. amboinicus was produced from the study. Another study reported using gamma-ray irradiation to evaluate the compounds profile from the leaves of P. amboinicus mutant compared with its wild-type (Aisyah et al 2020). From the hierarchical cluster analysis (HCA), they found that wild-type and mutant plantlets differed in their 2,3dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (DDMP), stigmasterol, and hydroxymethylfurfural contents.…”
Section: Introductionmentioning
confidence: 99%
“…Based on morphological changes, one putative mutant for P. amboinicus was produced from the study. Another study reported using gamma-ray irradiation to evaluate the compounds profile from the leaves of P. amboinicus mutant compared with its wild-type (Aisyah et al 2020). From the hierarchical cluster analysis (HCA), they found that wild-type and mutant plantlets differed in their 2,3dihydro-3,5-dihydroxy-6-methyl-4H-pyran-4-one (DDMP), stigmasterol, and hydroxymethylfurfural contents.…”
Section: Introductionmentioning
confidence: 99%
“…Coleus amboinicus is a member of the family of Lamiaceae, known to contain many clinically useful bioactive compounds such as flavonoids, alkaloids, tannins, triterpenoids and saponins (Damanik et al 2017;Aisyah et al 2020). This medicinal plant in Indonesia is called torbangun and has been traditionally used by Bataknese as a stimulant for breast milk (a lactagogue) (Damanik 2009).…”
Section: Introductionmentioning
confidence: 99%